Current Status and Issues with Kanji Learning in Community-based Japanese Language Classes - Hirata, Shiori (Intercultural Education, 2020)
To have an active social life in Japan, it is necessary to acquire the “Kanji reading and writing ability,” which is an essential element of the Japanese language. However, in community-based Japanese language classes, the main place where foreigners living in Japan learn Japanese, activities are mainly aimed at dialogue/ collaboration and mutual understanding. Correspondingly, little attention is given to provisions for Kanji learning support.In this paper, I present the results of a survey of nine classrooms which were visited to clarify problems with Kanji learning support in community-based Japanese classes. The results demonstrate that there are problems of awareness among teaching personnel, lack of manpower, and diversity of learners, all of which underlie the lack of support for Kanji learning.To provide effective support for foreign residents in Japan learning the Kanji syllabary, it is necessary to investigate learning methods that would be suitable to the philosophy of community-based Japanese language education.